Fault Diagnosis in Hybrid Renewable Energy Sources with Machine Learning Approach - Wang, Haoxiang (Journal of Trends in Computer Science and Smart Technology, 2021)
In recent days the need for energy resources is dramatically increasing world-wide. Overall 80% of the energy resource is supplied in the form of fuel based energy source and nuclear based energy source. Where fuel based energy resources are very essential in day-to-day life. Fossil fuel is also one among the energy resource and due to the high demand we face shortage in these resources. Providing electricity in rural areas is still a difficult process because of the shortage of energy resources. This issue can be rectified by choosing an alternate to electricity. To achieve this we have integrated many renewable energy sources to form a hybrid-renewable energy source system and this is capable of providing power supply to these areas. We have adopted artificial neural networks (ANN) technique based on machine learning to accomplish this process. For short-term prediction other techniques such as MLP, CNN, RNN and LSTM are used. These values are used as reference value in final execution.
Keywords: Hybrid-Renewable Energy Source; Artificial Neural Network (ANN); Fuel-Based Energy; Nuclear-Based Energy; Machine Learning